Sustainable utilization of palm oil industry by-products for livestock feed: A digestibility and environmental assessment - Arif Dwi Santoso; Evi Sribudiani; Atien Priyanti; Dwi Yulistiani; Hotmatua Daulay; Rahmania Hanifa; I Gusti Ayu Putu Mahendri; Priyono; Umi K. Yaumidin; Arsyadi Ali; Edi Erwan; Dudi Iskandar; et al. (Case Studies in Chemical and Environmental Engineering, 2025)
The palm oil industry generates substantial by-products with potential as alternative livestock feed. This study evaluated the digestibility and environmental impacts of two feed formulations: one combining oil palm fronds, solid decanter, and palm kernel cake, and another using oil palm fronds, palm kernel cake, and grated sago. Digestibility was assessed via the total collection method, while environmental performance was measured through openLCA 2.0 software, employing the CML-IA method with the Ecoinvent 3.8 database. The sago-based feed showed higher digestibility (65.71 %) but a poorer feed conversion ratio (16.81), primarily due to higher dry matter intake that increased overall feed consumption without a proportional gain in weight. Conversely, the solid decanter-based feed achieved better feed conversion ratio (11.53) but higher carbon emissions (223.415 kg CO2-eq/ton) compare with sago feed (197.243 kg CO2-eq/ton). In both feed formulations, feedstock mixing was identified as the dominant emission source, contributing over 99 % of total GHG emissions. These findings highlight trade-offs between nutritional efficiency and sustainability, emphasizing the need for low-impact ingredients and improved processing to optimize feed production.